Microstructural Characterization and Wear Properties of Fe-Based Amorphous-Crystalline Coating Deposited by Twin Wire Arc Spraying - Ana Arizmendi-Morquecho; Araceli Campa-Castilla; C. Leyva-Porras; Josué Almicar Aguilar Martinez; Gregorio Vargas Gutiérrez; Karla Judith Moreno Bello; L. López López (Advances in Materials Science and Engineering)
Twin wire arc spraying (TWAS) was used to produce an amorphous crystalline Fe-based coating on AISI 1018 steel substrate using a commercial powder (140MXC) in order to improve microhardness and wear properties. The microstructures of coating were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) as well as the powder precursor. Analysis in the coating showed the formation of an amorphous matrix with boron and tungsten carbides randomly dispersed. At high amplifications were identified boron carbides at interface boron carbide/amorphous matrix by TEM. This kind of carbides growth can be attributed to partial crystallization by heterogeneous nucleation. These interfaces have not been reported in the literature by thermal spraying process. The measurements of average microhardness on amorphous matrix and boron carbides were 9.1 and 23.85 GPa, respectively. By contrast, the microhardness values of unmelted boron carbide in the amorphous phase were higher than in the substrate, approaching 2.14 GPa. The relative wear resistance of coating was 5.6 times that of substrate. These results indicate that the twin wire arc spraying is a promising technique to prepare amorphous crystalline coatings.